Evaluation of antidiarrhoeal effects of Psidium guajava L. (Myrtaceae) aqueous leaf extract in mice - Salgado, Hérida Regina Nunes [UNESP]; Roncari, A. F F [UNESP]; Michelin, D. C. [UNESP]; Moreira, Raquel Regina Duarte [UNESP] (My University, 2006)
A crude aqueous extract of the leaves of the guava tree, Psidium guajava L. (Myrtaceae), were studied for antidiarrhoeal effects, to place one of its traditional medical uses. The extract induced a decrease in the propulsive movements of the intestinal contents in mice. These findings suggested that an aqueous extract of guava leaves may be used as an effective treatment for non-specific diarrhoea in folk medicine.
Keywords: Guava tree; in vivo test; Intestinal motility; Psidium guajava L. (Myrtaceae); plant extract; psidium guajava extract; sodium chloride; unclassified drug; animal experiment; animal model; controlled study; diarrhea; drug mechanism; female; guava; intestine motility; mouse; Myrtaceae; nonhuman; plant leaf